The Catholic internet television in thought legal-canonical of the Churc - DOMASZK, ARKADIUSZ (Prawo Kanoniczne, 2018)
The contemporary television is also available online. More and more television stations broadcast a typical signal of specific wave frequency and, simultaneously, broadcast the whole program lineup or particular shows on the Internet. Together with a classic form of television, there are TV stations developing which are operating online only. First of all, the article showed the norms of canonical law referring to the issues of television and, especially, Catholic programmes and stations. Second, the Catholic presence in Polish TV stations was outlined. Third, the last part of the article presented the TV presence of different Catholic subjects online (in Polish). The norms of universal canonical law are to a very small extent directly referring to the issue of television and are not discussing the problems of the Internet television at all. More specific regulations can be found in the documents issued by the Polish Bishops' Conference and particular Churches, among others, in the form of instructions. In the Polish media reality, the most visible is Trwam station as well as Catholic programs in the public television. Currently, a rapid development of different types of online television can be noticed. The Internet stations are established on the initiative of particular Churches, church movements and private individuals. They often broadcast the selected church events. Usually, there is no continuous signal but a wide selection of different programmes to be played. On the basis of analogy, the presented Internet stations should be subject to the teaching of Magisterium and the norms of canonical law. However, the aspect of a Catholic dimension of some of the stations might be debatable. If the Internet TV stations want to use the "Catholic" word, they should apply to a diocesan bishop for acceptance. What is more, it would be advisable to ask for a church assistant, especially in relation to church movements. And information of recognizing the television as Catholic and appointing a church assistant should be available at the station's website. To sum up, an increasing number of internet television initiatives of Catholic groups, movements and the faithful constitutes a contemporary form of new evangelization. The initiatives are a form of preaching the Gospel "at the roof of the global village", that is the world we are living in.